PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA TEMA PRAJA MUDA KARANA DI KELAS III SD PAB 23 PATUMBAK - Wiky Syahfitri; Tiflatul Husna (Bajang Institute, 2025)
This study aims to determine the effectiveness of the Make a Match cooperative learning model to improve student learning outcomes in thematic learning theme 8